ChemInform Abstract: Synthesis of 1, 2‐Dihydro‐2‐oxo‐4‐quinolinyl Phosphates from 2‐Acyl‐benzoic Acids. Issue 27 (18th June 2015) - He, Xinhua; Aglio, Tharcilla; Deschamps, Jeffrey R.; Rai, Rachita; Xue, Fengtian
Abstract A practical method to synthesize the title compounds starting from readily available starting materials is described.